CONTRADICTIONS AND LEGAL CERTAINTY IN HANDLING CHILD SEXUAL ABUSE IN ACEH: NATIONAL LAW AND SHARIA PERSPECTIVES - Rabiatul Hadawiah Lubis; Faisal Faisal (International Journal of Cultural and Social Science, 2025)
Law No. 44/1999 on the Implementation of Aceh's Specialty and Law No. 11/2006 on the Government of Aceh authorize Aceh to formulate its own criminal law products based on Islamic Sharia. This research discusses the contradiction in the regulation of punishment against perpetrators of sexual abuse against children in Aceh which is regulated in Qanun Jinayat and national laws and regulations such as the Criminal Code, Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, and Law No. 35 of 2014 concerning Child Protection. This paper uses a juridical-normative approach by focusing on juridical analysis and a legal philosophy approach by examining the concept of legal certainty in a normative- positivistic perspective and legal certainty in an Islamic perspective. The results of this study indicate that synchronization between national law and sharia law in Aceh is needed to eliminate norm inconsistencies that can weaken the effectiveness of law enforcement. The Attorney General's Office in Aceh as a Law Enforcement Official also needs to change the prosecution paradigm that prioritizes the interests of the perpetrator to be more in favor of the victim. Because, in Islamic law, the purpose of punishment is not only limited to retribution, but also includes prevention (deterrence), repair (reformation), and education for the community (al-tahzib). Therefore, ideally, the regulation of criminal law in Aceh is not only oriented towards formal legal certainty, but must also pay attention to aspects of benefit so that the law can provide more effective protection for victims.